Anestetici locali per microinfusione intratecale continua: efficacia vera o presunta? - Continuous microinfusion intrathecal local anesthetics: real or perceived effectiveness? - Guido Orlandini; Marco La Grua (Publiediting, 2012)
In this review the knowledge about the mechanisms underlying the local anesthetics action, the validity of their efficacy, the relationship among the anesthetic effect duration, the doses used, the administration pathways - particularly those concerning the continuous intrathecal infusion, and their sites of action are presented. It is highlighted that among the various sites described, the action at synaptic level could explain results obtained with very low doses that can be reached through systemic or spinal slow administration. Furthermore, this kind of action could also explain the plurimetameric effect comparable to that of morphine, which is known to act at synaptic level, other than the potentiating action on the opioid effects administered intrathecally and the usual observation of a control of "non-incident pain" and not of "incident pain".